Between Black mothers and daughters: a critical intergenerational duoethnography on the silence of health disparities and hope of loud healing - Winfield, Asha S.; Hickerson, Hope; Doub, Deshara C.; Winfield, Ann R.; McPhatter, Brigitte (Frontiers in Communication, 2024)
This original research article utilizes lived experiences through family storytelling to explore generations of Black American women's health narratives. Black women's health outcomes have been altered by a number of factors including social determinants of health, lack of healthcare providers, systemic and institutional levels of medical racism, and the lack of advocates who would empower Black women patients' voices for varied treatments. In fact, generations of Black American women, regardless of age, sex, location, region, religion, education, and socioeconomic status have either consciously or unconsciously participated [willingly or unwillingly] in the spiral of silence. Building off of (Anonymized)'s 2022 defining moments essay, Body, Blood, and Brilliance: A Black Woman's Journey to Loud Healing & Strength, authors write themselves into the narrative of Black American womanhood in search of better health after decades without. Two Black women scholars whose work sits at the nexus of Black culture, public health, and health communication, engage in critical intergenerational double duoethnography with their Black mothers who represent women in their 70s and 60s. Their lived experiences reveal the very real impacts of culture, identity, and power. By interrogating the past with stories, this group of Black mothers and daughters represent three generations of medical erasures.